3y+4+6x-3x-2y-2=

Simple and best practice solution for 3y+4+6x-3x-2y-2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y+4+6x-3x-2y-2= equation:


Simplifying
3y + 4 + 6x + -3x + -2y + -2 = 0

Reorder the terms:
4 + -2 + 6x + -3x + 3y + -2y = 0

Combine like terms: 4 + -2 = 2
2 + 6x + -3x + 3y + -2y = 0

Combine like terms: 6x + -3x = 3x
2 + 3x + 3y + -2y = 0

Combine like terms: 3y + -2y = 1y
2 + 3x + 1y = 0

Solving
2 + 3x + 1y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + 3x + -2 + 1y = 0 + -2

Reorder the terms:
2 + -2 + 3x + 1y = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 3x + 1y = 0 + -2
3x + 1y = 0 + -2

Combine like terms: 0 + -2 = -2
3x + 1y = -2

Add '-1y' to each side of the equation.
3x + 1y + -1y = -2 + -1y

Combine like terms: 1y + -1y = 0
3x + 0 = -2 + -1y
3x = -2 + -1y

Divide each side by '3'.
x = -0.6666666667 + -0.3333333333y

Simplifying
x = -0.6666666667 + -0.3333333333y

See similar equations:

| 10y-6x+4-4x+6y-6= | | 5y-2y+5x+4x-7+9= | | b*c*d*c= | | 3y-1-2y-2x+8-4x= | | a*b*-3*-3= | | 64-6x=8-10x | | p*6*q*-1= | | -3*n*2*m= | | -2*4*m*m= | | y=x^2+(m-1)x+4 | | c*c*3*b= | | 4*a*b*4= | | m*2*n*3= | | c*c*c= | | b+4/4-b-10/2 | | b*b*a= | | 48x^2-8x^3=0 | | 7y^2-7y-15=0 | | 41-7x=2x+21 | | 6-9x=78-38x | | 4(c+3)=-4 | | 4(3+3)=-4 | | 10m=80 | | 11x+21=2x+237 | | 9x-6=10x | | 7x+14=5x+70 | | 5x+10=90+3x | | 11x-272=2x-11 | | 16x-312=6x-12 | | 57-3x=24x+18 | | -90-7x=37-21x | | 10-8x=55-29x |

Equations solver categories